Analisis Pengaruh Beban Kerja, Budaya Organisasi, dan Lingkungan Kerja Non Fisik terhadap Kinerja Guru di Ichthus School West Jakarta Barat - Magda Pangesa; Theresia Pradiani; Fathorrahman Fathorrahman (Jurnal Pendidikan Indonesia, 2025)
Ichthus School West, Jakarta Barat, as an educational institution, has experienced a decline in teacher performance over the past few years. The phenomenon underlying this research includes the high workload of teachers exceeding the standard classroom hours, an organizational culture that tends to maintain traditional practices, and a non-physical work environment demanding intensive communication outside working hours, all of which contribute to decreased performance. This study aims to identify and analyze the influence of workload, organizational culture, and non-physical work environment on teacher performance at Ichthus School West, Jakarta Barat. A quantitative approach was employed, with data collected through questionnaires and sampling conducted using a purposive sampling technique, involving 40 teachers of written subjects at Ichthus School West, covering elementary and secondary (junior and senior high school) levels. The data were processed using multiple linear regression analysis and tested through instrument tests, classical assumption tests, determination tests, and hypothesis tests. The results reveal that workload has a negative and significant impact on teacher performance, organizational culture has a positive but insignificant impact, and the non-physical work environment has a positive and significant impact on teacher performance. Collectively, workload, organizational culture, and non-physical work environment have a positive and significant influence on teacher performance.